Analisis Pembangunan Ekonomi Inklusif dan Faktor Pendorong di Provinsi Papua - Pisi Bethania Titalessy; Radian Januari Situmeang; Herlina Irianti Mulyono; Richard Patty (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
Papua Province, known for its abundant natural resources and cultural diversity, faces significant challenges in achieving inclusive economic development. Persistent disparities in income, infrastructure, and access to essential services have hindered equitable growth and social welfare improvement. This study examines the inclusiveness of economic development in Papua and explores its driving factors. Utilizing secondary data from the Ministry of National Development Planning/National Development Planning Agency (Badan Perencanaan Pembangunan Nasional, Bappenas), BPS - Statistics Indonesia (Badan Pusat Statistik, BPS), and the Directorate General of Fiscal Balance (Direktorat Jenderal Perimbangan Keuangan, DJPK) for 2017–2021, the research employs descriptive analysis and panel data regression methods. The panel regression results highlight the critical role of fiscal policies in promoting inclusivity. Economic expenditures demonstrate a positive and significant impact on inclusive development, fostering equitable economic participation and productivity. In contrast, basic infrastructure spending shows a significant negative effect, possibly due to uneven allocation or misalignment with local community needs. While education expenditures are not statistically significant, they exhibit potential for enhancing inclusivity through long-term human capital development. These findings underscore the importance of targeted and well-distributed fiscal policies to address Papua’s unique socio-economic challenges. By prioritizing human capital, aligning infrastructure investments with local needs, and fostering balanced economic growth, policymakers can pave the way for more inclusive development across the province. This research provides valuable insights for designing effective policy interventions to reduce inequality and foster sustainable economic growth in Papua.